Answer:
A) t = -3
Explanation:
We have the expression
and we have to find the value of t.
First we are going to reorder the expression:
![((t-12))/(2)=(3t)/(2)-3\\\\3=(3t)/(2)-((t-12))/(2)\\\\3=(3t-t-(-12))/(2)\\\\3=(2t+12)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t32id0v8b99n2kqk0r01iy3j63aexcgy8a.png)
Now we have to multiply each side by 2,
![3=(2t+12)/(2)\\\\3.2=(2t+12)/(2).2\\\\6=2t+12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jj7wnkckckinydp93o9c7x09upw6lpua7p.png)
Subtract (-12) in both sides,
![6=2t+12\\6-12=2t+12-12\\-6=2t](https://img.qammunity.org/2020/formulas/mathematics/middle-school/osjqkg4x532udjif8e3jzp6zqgmhcz94yk.png)
Divide both sides in 2,
![-6=2t\\(-6)/(2) =(2t)/(2) \\-3=t](https://img.qammunity.org/2020/formulas/mathematics/middle-school/r0y49xlrd7zz7e67k3btvai8099n2fv5bc.png)
The answer is option A) t = -3.